IMPACT OF INFORMATION TECHNOLOGY INVESTMENT TO FINANCIAL PERFORMANCE ON BANKING SECTOR - Hendra Gunawan; Serlyna Serlyna (Pusat P2M Politeknik Negeri Batam, 2018)
This study examines the impact of technology on the performance of financial investment in banking companies listed in Indonesia Stock Exchange to prove its influence on the development of the banking company's financial performance. The data used in this research is secondary data uses financial statements that have been audited. Data analysis technique used is simple regression analysis. Results showed that between investments in information technology affect the company's financial performance. The results of this study illustrate that the company's financial performance would be if the investment in information technology in the company are used effectively and efficiently. This research is important for companies and organizations, in order to better the use or utilization of information technology in the enterprise. The company is only limited to the banking companies listed in Indonesia Stock Exchange, then further research is recommended to add criteria and indicator others that have not been addressed in this study, in addition to subsequent authors can also extend the sample population to another company with a different field such as manufacturing companies.